Towards a taxonomically unbiased EU Biodiversity Strategy for 2030 - Mammola, Stefano; Riccardi, Nicoletta; Prié, Vincent; Correia, Ricardo; Cardoso, Pedro; Lopes-Lima, Manuel; Sousa, Ronaldo (Dryad, 2020)
Through the Habitats Directive (92/43/EEC) and the LIFE projects financial
investments, Europe has been the world’s experimental arena for biological
conservation. With an estimated budget of €20 billion/year, the EU
Biodiversity Strategy for 2030 has set an ambitious goal of reaching 30%
Protected Areas and ensure no deterioration in conservation trends and
status of all protected species. We analyzed LIFE projects focused on
animals from 1992 to 2018 and we found that investment towards vertebrates
has been six times higher than that for invertebrates (€970 vs €150
million), with birds and mammals alone accounting for 72% species and 75%
total budget. Budget allocation is primarily explained by species’
popularity. We propose a roadmap to achieve unbiased conservation targets
for 2030 and beyond.
We extracted information on the amount of funding allocated to various
species using the LIFE projects database (https://ec.europa.eu; accessed
between February and May 2020). Note that we focused here on a
species-level conservation approach [9], in contrast to other more general
conservation measures (such as socio-ecological approaches [15,16] and
others [17]) that are only indirectly covered by LIFE projects. We first
filtered LIFE projects specifically aimed at species conservation, using
the query STRAND = “All”; YEAR = “All”; COUNTRY = “All”; THEMES =
“Species”; SUB-THEMES = “Amphibians”; “Birds”; “Fish”; “Invertebrates”;
“Mammals”; “Reptiles”. This query resulted in 819 LIFE projects that met
the search criteria. A second query focused on THEMES = “Biodiversity
issues”; SUB-THEMES = “Ecological coherence”; “Invasive species”; “Urban
biodiversity”, which matched an additional 298 LIFE projects. For the
latter query, we examined summaries of the LIFE projects and extracted
further information only from those specifically aimed at the conservation
of animal species (n = 16). For example, projects aimed at generically
enhancing biodiversity through measures targeting ecosystems or the
impacts of anthropic activities were not considered. In total, we included
835 projects in our analyses—819 with the theme “Species” and 16 with the
theme “Biodiversity issues”. To define the amount of funds allocated to
each species for each LIFE project, the budget of each project with
multiple species was divided equally among the target species. To obtain a
deeper understanding of the factors underlying the observed pattern of
conservation measures among species, we further associated traits to each
species (risk of extinction, body size, and online popularity).
See main text for details.
Data: Tab-delimited .csv file (See R script for the description
of relevant columns.) Code: .R file
Keywords: FOS: Biological sciences; European Union; LIFE project; Habitat Directive; vertebrate; Invertebrate; conservation investment